Characteristics of Salted Catfish (Pangasius hypophthalmus) with the Addition of Green Tea and Lemongrass - Mardalisa, Mardalisa; Hasanah, Alqoriffah; Amani, Mutia Dhiya; Permata, Bella (Faculty of Fisheries and Marine, Universitas Riau, 2022)
This study aims to characteristics the salted catfish after the combination of adding green tea and lemongrass. The research method used a randomized block design (RAK) which involved one treatment factor with 3 repetitions so that there were 12 units. The factors used in the treatment were 3% salt solution, 1% green tea and 0,15% lemongrass. This study stated that there was no significant effect of the four treatment levels on the results of the assessment of yield, ash content, water content, lipid content and protein content in salted catfish produced. Sensory analysis on the appearance, taste, aroma, and texture aspects showed that the treatment result had a significant effect only on the appearance aspect. The best product was found in the X2 treatment (3% salt solution dan 0.15% lemongrass) which resulted in a yield value of 57,25%, ash content 24,42%, water content 2.21%, lipid content 29,53%, and protein content 42,96%. Sensory analysis scores for appearance were 7,33 (whole, clean, lusterless), aroma 6,54 (neutral, little additional odor), taste 6,62 (good, species specific, little taste addition), and texture 6,93 (dense, no brittle).